The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1080/00016350050217163
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone and cortisol in serum and saliva

Abstract: Salivary diagnosis is a developing area in clinical chemistry and dentistry. Cortisol analyses from saliva have been used in pediatric practice and as doping tests. Growth hormone (hGH), also a stress hormone, has not been analyzed from saliva. We studied the serum and saliva of 51 healthy subjects. The samples were taken at 8:00 in the morning after 12 h fasting. Cortisol concentrations were analyzed using RIA. An immunoradiometric assay was applied for analyzing serum and salivary hGH. The validity of this m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 11 publications
2
21
0
4
Order By: Relevance
“…• There is autonomous production of ghrelin by the salivary glands, as has been shown for other hormones and growth factors (35,36 ). We could demonstrate production of ghrelin mRNA in all major salivary glands and in oral keratinocytes.…”
Section: Discussionsupporting
confidence: 65%
“…• There is autonomous production of ghrelin by the salivary glands, as has been shown for other hormones and growth factors (35,36 ). We could demonstrate production of ghrelin mRNA in all major salivary glands and in oral keratinocytes.…”
Section: Discussionsupporting
confidence: 65%
“…Sporadic reported investigations have demonstrated the presence of these 2 peptides in saliva (74,75 ) at very low concentrations (‰ of plasma concentrations).…”
Section: Salivary Hormones In Sports Medicinementioning
confidence: 99%
“…While one report of T4 in saliva found no correlation with serum levels [91], another study showed a significant correlation between salivary and serum T4 [92]. Salivary growth hormone was shown in one study to generally correlate with serum levels, but since its concentrations are 1000 fold lower than serum values, testing saliva for GH is difficult [93]. Salivary IGF-1 has been found to generally reflect growth hormone levels, being low in GH-deficient subjects and high in acromegalics when compared to controls [94]; however, its sensitivity for diagnosing acromegaly is very poor, with nearly half of acromegalic patients in one study having salivary IGF-1 concentrations within the normal range [95].…”
Section: Salivamentioning
confidence: 98%